2002
DOI: 10.1258/002221502761698748
|View full text |Cite
|
Sign up to set email alerts
|

Computer imaging and patient satisfaction in rhinoplasty surgery

Abstract: The measurement and achievement of improved patient benefit following a particular medical or surgical intervention has become an increasingly relevant part of the provision of effective healthcare. We have retrospectively analysed patient satisfaction in 56 patients following rhinoplasty via the Glasgow Benefit Inventory (GBI), 25 of whom underwent pre-operative computer imaging planning. We have also audited patient reaction to this technique via a concurrent questionnaire in those subjects who underwent ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 9 publications
0
34
0
1
Order By: Relevance
“…[59][60][61][62][63] This inventory measures the change in psychological, social, and physical well-being produced by surgical interventions 64 and could be a useful tool in future research. To define patients' expectations and their feasibility, there is a high need of a preoperative questionnaire to measure patients' expectations concerning the surgical and social outcome.…”
Section: Assessment Instrumentsmentioning
confidence: 99%
“…[59][60][61][62][63] This inventory measures the change in psychological, social, and physical well-being produced by surgical interventions 64 and could be a useful tool in future research. To define patients' expectations and their feasibility, there is a high need of a preoperative questionnaire to measure patients' expectations concerning the surgical and social outcome.…”
Section: Assessment Instrumentsmentioning
confidence: 99%
“…These papers discuss the effectiveness of the various elements of computer imaging simulations in rhinoplasty, including patients' satisfaction, confidence, and expectations, accuracy of preoperative manipulations compared with postoperative results, medico-legal implications of equipment, and limitations. [3][4][5][6] Despite all benefits, morphing has not yet been fully incorporated into routine rhinoplasty practice. Dissenting perspectives focus on the additional time required, complexity of imaging software, and the potential exposure to increased medico-legal risk.…”
mentioning
confidence: 99%
“…In the exclusively aesthetic group, there was a 152.7 mean difference. Finally, Sharp et al 20 also reported a successful outcome in rhinoplasty patients. However, their patients were also not a homogenous group, as they had undergone aesthetic 6 functional rhinoplasty.…”
Section: Discussionmentioning
confidence: 93%